Economic and Psychosocial Impact of COVID-19 in the Hispanic Community Health Study/Study of Latinos (Mary Ann Liebert, 2023)
Objectives: To examine the prevalence and correlates of economic hardship and psychosocial distress experienced during the initial phase of the coronavirus disease 2019 (COVID-19) pandemic in a large cohort of Hispanic/Latino adults. Methods: The Hispanic Community Health Study/Study of Latinos (HCHS/SOL), an ongoing multicenter study of Hispanic/Latino adults, collected information about COVID-19 illness and psychosocial and economic distress that occurred during the pandemic (N=11,283). We estimated the prevalence of these experiences during the initial phase of the pandemic (May 2020 to May 2021) and examined the prepandemic factors associated with pandemic-related economic hardship and emotional distress using multivariable log linear models with binomial distributions to estimate prevalence ratios. Results: Almost half of the households reported job losses and a third reported economic hardship during the first year of the pandemic. Pandemic-related household job losses and economic hardship were more pronounced among noncitizens who are likely to be undocumented. Pandemic-related economic hardship and psychosocial distress varied by age group and sex. Contrary to the economic hardship findings, noncitizens were less likely to report pandemic-related psychosocial distress. Prepandemic social resources were inversely related to psychosocial distress. Conclusions: The study findings underscore the economic vulnerability that the pandemic has brought to ethnic minoritized and immigrant populations in the United States, in particular noncitizens. The study also highlights the need to incorporate documentation status as a social determinant of health. Characterizing the initial economic and mental health impact of the pandemic is important for understanding the pandemic consequences on future health. Clinical Trial Registration Number: NCT02060344